Nuda a praktyczna nauka języka angielskiego - Kruk, Mariusz; Zawodniak, Joanna (Neofilolog, 2017)
Although boredom is among the most common academic emotions experienced by students at all possible levels of education, so far it has not received due attention from SLA theorists and researchers. Accordingly, the present paper aims to discuss the concept of boredom from the L2 classroom perspective with a special regard to the university students of English Philology. In the first part the authors provide a definition, present two basic typologies and highlight the causes of boredom followed by a brief overview of research into boredom in educational settings, whereas the second part is intended to approach a phenomenon of boredom on an empirical basis. The authors report on both quantitative and qualitative research findings concerning the intensity of boredom as felt by the subjects during the practical English language classes. First, the numerical results obtained from the Boredom Proneness Scale and correlated to boredom experienced in practical English language classes are referred to. Then the qualitative data gathered from the students’ descriptions of boredom-related situations during the said classes are commented on. Finally, the authors proceed to propose certain L2 classroom boredom-coping options.